First report of basal stem rot caused by three Fusarium species on Chinese yam in China - Li, Shaojian (Plant disease, 2024)
The cultivated variety of Chinese yam (Dioscorea polystachya Turcz. cv. Tiegun) is an economically important plant, capable of producing tubers that are used as food and traditional Chinese medicine. The basal stem rot was found on approximately 65% of yam (tuber expansion stage) in a total of 10 ha field in Wuzhi, Wen, and Hua counties, Henan, China (Sep 2021). Dark brown fusiform lesions initially occurred at the stems basal, irregularly extending to join together and leading to loop-stem necrotic indentation. Three diseased samples from Wuzhi county were collected, cut into 5 × 5 mm pieces, surface sterilized in 75% ethanol (30 s) and 1% NaClO (1 min), washed in sterile water 3 times, and placed on PDA in the dark for 3 days at 28℃. A total of 44 isolates forming three groups of Fusarium colonies were obtained using monosporic isolation, of which 19, 8, and 17 isolates were identified as F. oxysporum, F. solani, and F. proliferatum based on colony morphology, respectively. Typical isolates SYJJ6, 9, and 10 for each group were further studied. The SYJJ6 colonies showed gray white abundant fluffy aerial mycelium with rough edges, formation of ellipsoid, unicellular microconidia without septa, 5.6 to 13.4 × 2.4 to 4.7 μm (n = 50), and sickle-shaped, slightly curved macroconidia with 2 to 4 septa, 14.0 to 23.9 × 3.4 to 5.1 μm (n = 50). Isolate SYJJ9 produced flocculent white colonies, grew in a circular pattern with a sharp edge, forming oval or oblong microconidia with zero or one septum, 11.2 to 18.8 × 3.4 to 6.2 μm (n = 50), and slightly curved macroconidia with 2 to 3 septa, 27.6 to 44.0 × 3.9 to 7.4 μm (n = 50). SYJJ10 produced whitish or pinkish white colonies with fluffy aerial mycelium and a red pigmentation, produced renal or oval microconidia with no septa, 5.1 to 11.8 × 1.8 to 4.2 μm (n = 50), and falcate, slightly curved macroconidia with 3 to 4 septa, 16.1 to 30.2 × 3.1 to 5.9 μm (n = 50). Additionally, TUB, EF-1α, and RPB2 genes were amplified with primers BT2a/BT2b, EF1/EF2, and 5f2/-7cr, respectively (Glass and Donaldson 1995; O'Donnell et al. 1998, 2010). BLASTn analysis on SYJJ6 (OR047663, OR047666, OR047669), SYJJ9 (OR047665, OR047667, OR047670), and SYJJ10 (OR047664, OR047668, OR047671) gene sequences were over 99% identical to those of F. oxysporum (100%, MK432917; 100%, MN417196; 99.61%, MN457531), F. solani (100%, MF662662; 100%, MN223440; 99.80%, CP104055), and F. proliferatum (100%, ON557521; 100%, ON458137; 99.90%, LT841266), respectively. Pathogenicity tests of three isolates were separately performed on 60-day-old yam seedlings. The basal stems were wounded using needle, and the wounds were wrapped with cotton balls soaked with conidial suspension (1 mL, 3×106 conidia/mL) or water (control). Each isolate treated three plants and repeated three times. All plants were grown at 28℃ under a 16/8-h light/dark cycle. Typical symptoms emerged on basal stems at 16, 13, and 17 days after inoculation with the conidia of isolates SYJJ6, 9, and 10, while the control basal stems appeared healthy. The re-isolated fungi were identical to the original three isolates. Fusarium species (F. oxysporum, F. commune, F. humuli, etc.)were previously reported to cause wilt or stem rot on different D. polystachya cultivars (Fang et al. 2020; Li et al. 2023; Zhao et al. 2013), or basal stem rot on Panax ginseng (Ma et al. 2020). This is the first report of Chinese yam basal stem rot caused by Fusarium species, which threatens the production of Chinese yam 'Tiegun' and should be further studied